O CUCA e a acessibilidade: espaço, memória e patrimônio feirense frente às adaptações para o uso contemporâneo - Ferreira, Gabriel Silva (2025)
The adaptations made to the University Center of Culture and Art (CUCA) in Feira de Santana were evaluated and discussed in light of their usability for contemporary demands. Initially, a brief overview was provided of the most relevant historical contexts and facts that defined its particularities as a tangible and intangible heritage of the city, supported by its memory and eclectic architecture. The objective of this research is to assess the internal accessibility of the CUCA, whose importance lies primarily in serving people with disabilities (PWD) and reduced mobility in cultural spaces of this nature. To this end, an analysis of the characteristics of its various buildings was undertaken, and this approach was conducted in accordance with IPHAN Normative Instruction No. 1 of 2003; NBR-9050; Federal Decree No. 5,296 of 2004; and Federal Law No. 13,146 of 2015. Thus, CUCA was also considered a public heritage site listed by IPAC-BA, as a historic site of the Normal School from 1927, as well as a site that housed other important institutions, such as the Feira de Santana-BA School of Education from 1969, the embryo of the Feira de Santana State University (UEFS). Currently, CUCA is the implementation unit of UEFS's cultural policy and has been relevant in the promotion of artistic and educational activities since its inauguration in 1995. The results of this research were obtained through the evaluation of eight accessibility items, based on an analysis guide developed by Castro (2022), listing essential elements of a building, such as the good condition of the sidewalks adjacent to the building, the layout of entrances and internal accessible routes, the conformity of service counters, the existence of accessible restrooms and visual and tactile signage, the availability of exclusive parking spaces, as well as the existence of an elevator or lifting platform, since the unit has two floors and considerable differences in level. Along with the important contributions of Cambiagui (2012), Barbosa and Albuquerque (2010), Bueno and Guedes (2019), Prates (2015), and Tojal (2020), this case study revealed that accessibility conditions in the internal space of CUCA are lacking in accordance with accessibility standards and current legislation; therefore, they do not offer full safety, autonomy, and comfort for the public, specifically for PcD.